ANALISIS PENDAPATAN USAHATANI JAGUNG MANIS DI DESA LABUAN INDUK KECAMATAN LABUAN KABUPATEN DONGGALA - Isran, Isran; Kalaba, Yulianti; Sulaeman, Sulaeman (AGROTEKBIS, 2018)
This study aims to determine the amount of farmers income on the sweet corn farming in the village of Labuan Induk, Labuan subdistrict, Donggala Regency. The study was conducted from April to June 2016. The determination of sampling method used simple random sampling method (Simple random sampling method) by taking 30 respondents out of 96 people a corn farmer in the village of Labuan Induk. The analysis method used is the analysis of income. Results of the analysis showed that an average acceptance of sweet corn growers in the farm of the village of Labuan Induk is Rp 10.3075 million / 0.52 ha / PS or USD 19,822,115.4 / ha / PS and an average income of Rp 5818 .747,27 / 0.52 ha / PS or Rp11.189.898,6 / ha / PS.Â Keywords: Desa Labuan Holding, Sweet Corn, Revenue